Decision support system using system dynamics simulation modelling for projection of dentist supply - A. Samah, Azurah (2014)
This paper describes the development of a decision support system (DSS) using System Dynamics (SD) simulation approach to project and analyse the supply of dentist at both local and private Malaysian healthcare provider from 2015 to 2030. The project was driven by the need to provide sustainable, quality dental services in a complex environment given fluctuations in dental graduate numbers, migrations, attritions and activities. The developed DSS using VENSIM software described in this paper is flexible and expandable. It can be used to monitor future changes in dental workforce and provide a comprehensive and structured policy analysis to policy-makers and health managers, within the Ministry of Health Malaysia.